The The Incidence of Mandibular Angle Fractures Accompanied by Impacted Third Molar at Oral Surgery Clinic of Hasan Sadikin Hospital, Bandung - West Java: Insidensi Fraktur Angulus Mandibular Yang Disertai Gigi Impaksi di Klinik Bedah Mulut Rumah Sakit Hasan Sadikin Bandung-Jawa Barat - Ryant Ganda Santoso; Sjamsudin, Endang; Adiantoro, Seto (TALENTA, 2022)
Mandibular fracture is a discontinuity of mandible bone that usually leads to trauma. The fractured area is mostly the mandibular angle located in the third molar area. Therefore, this study aims to examine the incidence of mandibular angle fractures accompanied by impacted teeth in the oral surgery clinic of Hasan Sadikin Hospital.Â This is a retrospective observational study and the data used were collected from the medical records of patients with mandibular angle fractures accompanied by impacted third molars at the Oral Surgery Clinic of Dr. Hasan Sadikin Bandung from January 2017 to December 2019. Panoramic radiographs were obtained for confirmation and the data collected were age, gender, fracture aetiology and location, impacted tooth type and classification, as well as treatment.Â The number of mandibular angle fractures with impacted third molars in male patients (92.8%) was more than in females (7.2%). Fractures caused by traffic accidents and fights were 85.8% and 14.2%, respectively, while all patients were treated with ORIF. The percentage of cases according to the classification of third molars in angle fractures are classes IA (20%), IB (6.7%), IIA (20%), IIB (20%), IIC (13.3%), IIIC (6.7%), and unerupted tooth seeds (13.3%).The incidence of mandibular angle fracture with impacted third molars at the Oral Surgery Clinic, Dr. Hasan Sadikin over the last three years has increased. This case is more common in males due to traffic accidents and is treated with surgery (ORIF).